SCOPING REVIEW: EFEKTIVITAS PENGGUNAAN FINTECH TERHADAP KINERJA UMKM INDONESIA - Gunibala, Zakir (Jurnal Ekonomi Bisnis Kompetif, 2025)
This scoping review aims to map existing research related to financial technology (fintech) on MSME performance in Indonesia. This scoping review follows the approach outlined by Arksey and O'Malley (2005), which includes: 1) determining the research question; 2) searching for relevant research; 3) selecting articles; 4) collecting data, and 5) collating, summarising and reporting results. The time span of the article is 2021-2024. The review found that fintech has significant positive impacts on various aspects of MSME performance, including improved financial performance, revenue, profitability, and sales. Fintech has also proven effective in overcoming financing constraints and improving access to capital for MSMEs. All articles reviewed have limitations, including the dominance of quantitative methods that may not fully capture the complexity of fintech adoption, and the lack of exploration of contextual factors such as digital infrastructure and government policies. For future research, it is recommended to conduct more in-depth qualitative studies and longitudinal analyses to understand the long-term effects of fintech, as well as explore the role of contextual variables that influence the effectiveness of fintech for MSMEs in Indonesia. Future literature reviews could focus on aspects of financial technology adoption, its relevance to financial inclusion and MSME behaviour, and factors that hinder the use of financial technology for MSMEs, especially in Indonesia.